A New Iterative Method for Finding Approximate Inverses of Complex Matrices - M. Kafaei Razavi; A. Kerayechian; M. Gachpazan; S. Shateyi (Abstract and Applied Analysis)
This paper presents a new iterative method for computing the approximate inverse of nonsingular matrices. The analytical discussion of the method is included to demonstrate its convergence behavior. As a matter of fact, it is proven that the suggested scheme possesses tenth order of convergence. Finally, its performance is illustrated by numerical examples on different matrices.